16‐1: Low‐Power Oxide‐Semiconductor Display System. Issue 1 (May 2017) - Kurokawa, Yoshiyuki; Kunitake, Hitoshi; Harada, Shintaro; Akasawa, Fumika; Okamoto, Yuki; Nakagawa, Takashi; Aoki, Takeshi; Yoneda, Seiichi; Inoue, Hiroki; Kozuma, Munehiro; Ikeda, Takayuki; Yao, Hai Biao; et al.
Abstract : An oxide semiconductor (OS) display system built with normally‐off devices, nonvolatile OS LSI and an OS display, is proposed. The power consumption of the system is reduced by the nonvolatile OS LSI performing power gating without vanishing setting data when the OS display is in an idling stop (IDS) mode.